2022
DOI: 10.1111/jam.15709
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal potential of Azotobacter species and its metabolites against Fusarium verticillioides and biodegradation of fumonisin

Abstract: Aims In the study, seven Plant Growth Promoting Rhizobacteria (PGPR) Azotobacter species were screened against three strains of Fusarium verticillioides to test its antifungal activity. Azotobacter strains were tested for the degradation of fumonisin produced by F. verticillioides. Secondary metabolites were isolated and characterized from the Azotobacter strains for the first time. Methods and Results Potential seven Azotobacter species antifungal activity was tested following the dual culture assay against t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…37,38 Another study also showed that 3 methyl 1 butanol and 2-phenylethyl methyl ether produced by R. aquatilis were effective in controlling C. gloeosporioides which causes infection in the leaves and fruits of many plants. 39,40 Therefore, nonadecene, octadecene, hexadecane, tetradecene, acetic acid, formic acid, and butyl ester are some of the compounds among the 39 antifungal compounds that have been identified in the current study, and which have also been proven to possess antifungal effects from previous studies.…”
Section: Discussionmentioning
confidence: 77%
“…37,38 Another study also showed that 3 methyl 1 butanol and 2-phenylethyl methyl ether produced by R. aquatilis were effective in controlling C. gloeosporioides which causes infection in the leaves and fruits of many plants. 39,40 Therefore, nonadecene, octadecene, hexadecane, tetradecene, acetic acid, formic acid, and butyl ester are some of the compounds among the 39 antifungal compounds that have been identified in the current study, and which have also been proven to possess antifungal effects from previous studies.…”
Section: Discussionmentioning
confidence: 77%
“…For cells of the genus Azotobacter , which are present in many methanogenic consortia ( Figure 2 and Figure 3 ), the activity against FUMs has been shown in a number of studies [ 113 , 114 ]. Probably, an increase in the number of these cells as components of improved variants of microbial communities can be considered for the destruction of mycotoxins in bird droppings within AD with the hope of success.…”
Section: Expected Potential In Development Of Anaerobic Biocatalysts ...mentioning
confidence: 95%